The impact of public financing on performance indicators of elementary education in Morocco - MEZENE, M’bark; EL KAMLI, Mohammed; EL OUARDIRHI, Sanae; EL OUARDIRHI, Saad (Revue Internationale du Chercheur, 2020)
The methodology to approach the field of education depends on the quality analysis and, above all, on its impact on the internal performance of the system and on the evaluation of different development policies. Meanwhile, it is important to take into account the macroeconomic and budgetary aspects that determine and resources available to reinforce the education system and the constraints as well. Hence, this analysis should focus on indicators that are assimilated into a methodological repertoire of several parameters that intentionally affect political decisions. The main objective of this article relies on valuing the use of analyses and econometric techniques in the field of social sciences. In particular for the realization of an analytical study and a forecasting study, in an attempt to measure and evaluate the impact of public financing of elementary education in Morocco and its impact on performance indicators, from a longitudinal perspective of 40 years, covering the period from 1979 to 2018.